Implementation of Change Management in Store X - Putra, Rangga Permana; Rudito, Bambang (The Indonesian Journal of Business Administration, 2014)
Abstract - The author doing the implementation management changes directly to the Store "X" located in Sukabumi, the company has been moving in this industry for 24 years. Changes that will be conducted the company namely, transformation that includes leadership, strategy, structure and culture and have the nature of revolutionary. If the, encounter of failure will lead to shocks in the company, so that the necessary the application of changes management in to manage them. This research describes how to perform the transformation and handling of resistance that will arise in making changes. The model used is Prosci's Change Management Process and The ADKAR model, because this model overall will guide agents of change in determining the stages of will be conduct in the process of change management. In the implementing the change, the process will be divided into two stages, the first stage is the introduction formulation of business requirements and designing concepts, the next is the second stage namely to apply and implementing. The Company has conducted a survey of its employees, amounting to 20 people. The results of the survey showed the awareness and the desire to make a change with the value of 3,35 and has a sufficient understanding of the changes with the value of 3,25. This change program will be succeed with attention to other factors like a planning and strategic namely, the implementation process and application the program of changes. The company has planned implementation of this change program during the term 18 months.Â Keywords : Change Management, Transformation, The ADKAR Model, Implementation